Challenges and Triumphs of Democratisation in Mongolia - Chatterjee, Souvik (Hasanuddin Journal of International Affairs, 2024)
The major socio-political change in Mongolia was the change of political system from one-party socialist to multi-party democracy in 1990s. The political liberalisation of ideas- the change of economic system, inauguration of the new constitution in 1992 and the first ever free parliamentary elections are the key features of the Mongolia’s Democratic revolution. The importance of researching democratic consolidation in Mongolia can be underscored in several keyways. Firstly, Mongolia serves as an exemplary case of a nation that has transitioned positively towards democracy in a global landscape where democracy often remains an outlier rather than the norm. From the events that Mongolia had to overcome and the knowledge that was gained, there is much to learn on how democratisation processes could be maintained in transitional societies. Qualitative research approach is fitting for this study since it enables the researcher to gain an insight into subjective experiences as well as perceptions of those who are either involved in or affected by a democratic transition in Mongolia. Findings of this research highlights Mongolia's democratisation process both possibilities as well as difficulties involved. Mongolia has done fairly well in terms of institutionalising democracy, but numerous challenges are still persistent which require continuous attention and concerted efforts being made towards addressing them. By introducing strategic reforms, endorsing comprehensive development, fostering transparency culture and nurturing a sense of accountability within state institutions Mongolia can reinforce further consolidation of its democratic gains.